PENGUASAAN KETERAMPILAN DASAR MENGAJAR MAHASISWA SELAMA MENGIKUTI PROGRAM PENGALAMAN LAPANGAN KEPENDIDIKAN (PPLK) MENURUT PERSEPSI GURU PAMONG MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FT UNP - 435-443 , Yuhendri . (Universitas Negeri Padang, 2014)
ABSTRACT The purposeof thisdescriptiveresearchis to identifyinghow are thestudentsbasicteachingskillsauthority in joining teaching practicePPLKaccordingguided teacher’s perception about students ofTechnical Building Educationinhalffrom July to December2013. The population in this research is 50 college students who are joining teaching practice program PPLK on Juli to Desember 2013. The sampling techniqueis done bysimple random sampling and obtained a sample of33 guided teachers. The data usedisprimary data. Primary data were obtainedfromsamplesthrough aquestionnairewithLikertscalemodels. Andanalysis ofdata usingmean andpercentageformula. In general, it can be seen from the guided teacher’s perception of the mastery of basic skill tutors teach students included in a good category. Keywords: basic teaching skill, skill authority, perception